Novel macromolecular inhibitors of human immunodeficiency virus-1 protease - Miklóssy, Gabriella (Oxford University Press, 2008)
An intracellularly expressed defective human immunodeficiency virus type-1 (HIV-1) protease (PR) monomer could function as a dominant-negative inhibitor of the enzyme that requires dimerization for activity. Based on in silico studies, two mutant PRs harboring hydrophilic mutations, capable of forming favorable inter- and intra-subunit interactions, were selected: PR(RE) containing Asp25Arg and Gly49Glu mutations, and PR(RER) containing an additional Ile50Arg mutation. The mutants were expressed and tested by PR assays, nuclear magnetic resonance (NMR) and cell culture experiments. The mutant PRs showed dose-dependent inhibition of the wild-type PR in a fluorescent microtiter plate PR assay. Furthermore, both mutants were retained by hexahistidine-tagged wild-type HIV-1 PR immobilized on nickel-chelate affinity resin. For the first time, heterodimerization between wild-type and dominant-negative mutant PRs were also demonstrated by NMR spectroscopy. (1)H–(15)N Heteronuclear Single Quantum Coherence NMR spectra showed that although PR(RE) has a high tendency to aggregate, PR(RER) exists mainly as a folded monomer at 25–35 µM concentration, but in the presence of wild-type PR in a ratio of 1:1, heterodimerization occurs with both mutants. While the recombinant virus containing the PR(RE) sequence showed only very low level of expression, expression of the viral proteins of the virus with the PR(RER) sequence was comparable with that of the wild-type. In cell culture experiments, infectivity of viral particles containing PR(RER) protein was reduced by 82%, at mutant to wild-type infective DNA ratio of 2:1.